Deconstructing Finance Management: A Qualitative Examination through Accounting Literature - Widarni, Eny lestari (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study examines the deconstruction of traditional financial management concepts through accounting literature, aiming to address the limitations of conventional approaches and propose adaptive frameworks that integrate social, cultural, and contextual dimensions. The research adopts a qualitative systematic literature review, synthesizing insights from Agency Theory and Institutional Theory to explore the interplay between internal governance mechanisms and external environmental pressures. The findings reveal significant areas for improvement in traditional financial models, such as Net Present Value (NPV) and Internal Rate of Return (IRR), which fail to account for managerial biases, organizational culture, and societal expectations. Accounting frameworks are pivotal in bridging these gaps by emphasizing transparency, accountability, and sustainability through sustainability reporting and socially responsible disclosures. Discussions highlight the influence of governance structures and external regulatory pressures in shaping ethical and adaptive financial practices. At the same time, managerial biases and cultural dynamics underline the need for a holistic approach to decision-making. This study offers practical implications for managers and policymakers, recommending the adoption of robust governance structures, enhanced accounting literacy, and integrative financial models that prioritize long-term resilience. While contributing to the academic discourse on financial management, this research identifies its limitations in empirical validation. It calls for future studies to explore longitudinal and cross-contextual analyses to enrich understanding further.